Ecological and economical impact of Bats on ecosystem - Ramteke Asha Vilas (International Journal of Life Sciences, 2016)
In an ecosystem diversity of organisms interact with each other and the species are evolving to increase their ability to withstand the rigors of the environment. Major ecosystems of world had threatened by human interference. The report emphasized in particular on beneficial role of bats in the environment as bats contribute in the maintenance of ecosystem. Bat species provide ecosystem services through pollination, seed dispersal and insect control, most importantly in tropical forests. The frugivorous bats plays vital role in the maintenance of species-rich tropical forests because of long distance dispersers of tropical seeds. Insectivorous bats, in particular suppress insect population in the environment, in agro ecosystem particularly as primary predators and natural controllers of night flying insects.